The first Neotropical and Afrotropical species of Microphorella Becker, with a key to the genera of Parathalassiinae and species of Microphorella from the Southern Hemisphere (Diptera: Dolichopodidae sensu lato) - Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2023)
Two new species of Microphorella Becker are described and illustrated from Chile and South Africa, respectively: M. amorimi sp. nov. (Maule Region) and M. irwini sp. nov. (Western Cape Province), representing the first formal records of the genus from the Neotropical and Afrotropical Regions. In addition, a key to the genera of Parathalassiinae and species of Microphorella from the Southern Hemisphere is also provided.